Preparation method of anti-cracking high-temperature-resistant cable material

By modifying the surface of glass fibers and deposition of titanium dioxide, combining montmorillonite and graphene to form a composite material, the problems of high temperature resistance and crack resistance of cable materials at extreme temperatures are solved, and the performance of cables is significantly improved.

CN119161677AInactive Publication Date: 2024-12-20JINGJIANG YABAO ELECTRIC HEAT DEVICES & MATERIALS CO LTD

Patent Information

Application Number
CN202411692485.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2024-12-20
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing cable materials show poor high temperature resistance, low strength and poor impact resistance under extreme temperature conditions, resulting in a shortened service life of the cable and an increase in safety hazards. The commercially available high temperature and crack-resistant cables cannot meet the current demand.

Method used

The glass fibers are surface modified by γ-methacryloyloxypropyltrimethoxysilane, and titanium dioxide is deposited through oleic acid encapsulation and atmospheric plasma jet, combining natural montmorillonite and graphene oxide to form a composite material, through Electrostatic adsorption and van der Waals force interaction improve the thermal stability and mechanical properties of cable materials.

Benefits of technology

The cable material has been improved with crack resistance and high temperature resistance. Through the combination of three-dimensional structure titanium dioxide and nano-scale montmorillonite-ferrooxide-graphene composite materials, the thermal stability and mechanical properties of the cable are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a preparation method of an anti-cracking high-temperature-resistant cable material, and relates to the technical field of wires and cables. According to the invention, the glass fiber is subjected to surface modification, and then the glass fiber is wrapped by oleic acid, so that the bonding strength of the glass fiber in polyvinyl chloride is improved; then, titanium dioxide is deposited on the surface of the glass fiber by using atmospheric pressure plasma jet, a water-oil interface is formed due to the existence of oleic acid on the surface, a sheet-shaped stacked polyhedral structure is formed, and the thermal stability and the mechanical property of the cable material are improved; carrying out secondary plasma treatment to generate chemical binding sites; secondly, activated sodium-based montmorillonite is magnetized and then combined with graphene oxide, and the composite material is reduced to be separated from oxygen atoms through high-temperature calcination to form a nanoscale composite material, so that the agglomeration of graphene in polyvinyl chloride is improved, and the high-temperature resistance is effectively improved. The cable material prepared by the invention has the effects of cracking resistance and high temperature resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electric wires and cables, and in particular to a method for preparing a crack-resistant and high-temperature resistant cable material. Background Art

[0002] Cables are usually made of one or more mutually insulated conductors with insulation and protective layers. They are used to transmit electricity or information from one place to another and are widely used in power systems. There are many types of cables, and they are widely used. Due to their daily use and large-scale applications, higher requirements are placed on the performance and quantity of cables. Therefore, the materials used to make cables are gradually becoming more high-end, specialized and special.

[0003] At present, cables are widely used in different regions and time and space, including under extreme temperature conditions. Most cables are installed between two electric poles and exposed to the outdoors. Once damaged, they will cause hidden dangers to the power supply system and people's safety. However, the performance of most cable materials is still not very ideal. During the use of cables, there are defects such as poor high temperature resistance, low strength, and poor impact resistance, which shortens the service life of the cables, increases economic pressure, and poses safety hazards. However, the currently available high temperature resistant and crack resistant cables cannot meet the current needs, so the present invention provides a crack resistant and high temperature resistant cable material and a preparation method thereof to solve the above problems. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a crack-resistant and high-temperature resistant cable material to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a method for preparing a crack-resistant and high-temperature resistant cable material, comprising the following preparation steps: (1) At 25°C, γ-methacryloxypropyltrimethoxysilane is mixed with deionized water and ethanol to prepare a modifier alcohol aqueous solution with a mass fraction of 2-8%, and after hydrolysis for 15-45 minutes, glass fibers accounting for 30-40% of the mass of the modifier alcohol aqueous solution are added, and the solution is immersed at 80-100°C for 6-10 hours, then taken out, and then placed in a vacuum drying oven at 120°C for 1-2 hours to fully react to obtain pretreated glass fibers; 1-2 parts of the pretreated glass fibers are added to 50 parts of deionized water, mechanically stirred at a speed of 60-100 rpm and heated to 80°C, and then 0.5-4 parts of oleic acid are added dropwise, and then the solution is kept warm for reaction for 6-10 hours. After the reaction is completed, the solid is taken out and washed with deionized water for 3 times to obtain oleic acid-coated glass fibers; (2) The oleic acid-wrapped glass fiber is fixed at a processing distance of 15-20 mm by adjusting the height of the moving platform, which is the length of the plasma jet flame. The moving speed of the moving platform is adjusted to control the processing time to 10-14 s. The working gas flow rate is fixed to 1-4 L / min. The flow meter is adjusted to control the carrier gas flow rate. The flow rate of titanium chloride is 20-60 mL / min, and the flow rate of water molecules is 80-120 mL / min. Turn on the AC power supply to excite the atmospheric pressure plasma jet to generate plasma. Titanium chloride vapor is mixed with the inert gas and enters the plasma jet discharge zone together with the water molecule vapor. It is transferred to the surface of the oleic acid-wrapped glass fiber along with the plasma jet flame to form titanium dioxide deposition. Then, the product after the deposition is modified and placed on a special transmission device of the plasma treatment equipment. Under atmospheric pressure and open environment, the plasma is directly sprayed onto the surface of the product at a power of 10-70 W for 20-60 s to prepare a glass fiber-titanium dioxide material. (3) Disperse 2-3 parts of natural montmorillonite into 50 parts of deionized water and stir at 400-600 rpm for 1-3 hours for activation, then add a certain amount of hexadecyltrimethylammonium bromide active agent to the montmorillonite suspension, and heat the mixed solution to 75°C and stir at 400-600 rpm for 2-4 hours; then filter the resulting solution, wash it with deionized water three times, and dry it at 60°C for 6-10 hours to obtain activated montmorillonite; weigh 2-5 parts of the activated montmorillonite into 50 parts of deionized water, and stir it magnetically at 150-250 rpm for 60-120 minutes at room temperature to obtain an activated montmorillonite suspension; weigh 0.5-1.5 parts of ferric chloride solid and dissolve it in 50 parts of deionized water, and dissolve it quickly by ultrasound to prepare a ferric chloride solution; slowly add the ferric chloride solution into the activated montmorillonite suspension by a peristaltic pump, and stir it at 100-200 rpm for 24 hours in a water bath at 60°C. h, after the reaction is completed, stirring is stopped, and aging at room temperature is continued for 12 hours; after aging, the solid is centrifuged at 18000rpm for 20 minutes, and the solid is repeatedly washed with deionized water for 3 times, and then dried at 70°C for 5 hours to obtain magnetic montmorillonite; 1 part of graphene oxide is mixed with 50 parts of deionized water to form a dispersion, and then ultrasonically treated for 30 minutes, and then 5-8 parts of magnetic montmorillonite are added, ultrasonically treated for 30 minutes, and then the mixture is fully stirred at 600rpm for 2 hours; the suspension after the reaction is filtered and washed with deionized water for 3 times, freeze-dried, and then calcined at 750-850°C for 1-2 hours, and the composite material is obtained after the calcination is completed; (4) Raw materials by weight ratio: 60-80 parts of polyvinyl chloride SG-3, 0.4-0.6 parts of silane coupling agent KH550, 15-16 parts of polypropylene resin, 2-4 parts of barium stearate, 2-3 parts of dimethylaminoethoxyethanol, 2-5 parts of composite material, 1-4 parts of glass fiber-titanium dioxide material, 2-4 parts of epoxy soybean oil, 1-2 parts of antimony trioxide, 5-8 parts of carbon nanotubes. The materials are mixed in proportion and placed in a centrifuge. After centrifugation and stirring at 500-700 rpm for 10-30 minutes to mix evenly, the temperature is 160-180°C, and the mixture is extruded into a molten state in a twin-screw extruder. After the mixture is completely melted, it is extruded into an injection molding machine to obtain a crack-resistant and high-temperature resistant cable material.

[0006] Furthermore, in the step (1), the mass ratio of deionized water to ethanol in the aqueous alcohol solution of the modifier is 1:5.

[0007] Furthermore, the vacuum degree of the vacuum drying oven in step (1) is 0.085 MPa.

[0008] Furthermore, the heating rate in step (1) is 10°C / min.

[0009] Furthermore, in step (2), the inert gas is argon.

[0010] Furthermore, during the modification in step (2), the atmosphere is helium or oxygen within a specific distance of 2 cm below the nozzle of the plasma jet device.

[0011] Furthermore, in step (3), the mass ratio of hexadecyltrimethylammonium bromide to montmorillonite is 0.05-0.25:1.

[0012] Furthermore, the ultrasonic power in step (3) is 20 kHz.

[0013] Furthermore, the freeze drying in step (3) is performed at -40°C for 12 hours.

[0014] Furthermore, in step (4), the extrusion temperature is 170-175°C.

[0015] Compared with the prior art, the beneficial effects achieved by the present invention are: The invention prepares a cable material using glass fiber-titanium dioxide and a composite material modified polyvinyl chloride with a three-dimensional structure as raw materials to achieve the effects of crack resistance and high temperature resistance.

[0016] First, the surface of the glass fiber is modified with γ-methacryloxypropyltrimethoxysilane to increase the active groups on the surface of the glass fiber, and then the glass fiber is wrapped by the reaction of oleic acid with the active groups on the surface. The glass fiber wrapped with oleic acid improves its bonding strength in polyvinyl chloride and more effectively exerts its mechanical properties of improving the crack resistance of the cable material; then, titanium dioxide is deposited on the surface of the glass fiber wrapped with oleic acid by using an atmospheric pressure plasma jet, and a water-oil interface is formed due to the presence of surface oleic acid. Titanium dioxide formed by dehydration condensation of titanium precursor and mist water molecules forms a polyhedral structure of stacked sheets with nanometer-scale reaction space. This three-dimensional structure of titanium dioxide improves the thermal stability and mechanical properties of the cable material; and then a secondary plasma treatment is performed, in which the spray plasma not only forms free radicals on the surface of titanium dioxide, but also forms depressions on the surface of titanium dioxide due to the impact of ion beams, providing chemical binding sites, which is beneficial to the subsequent bonding of composite materials; Secondly, natural nano-montmorillonite is first dispersed in water for activation, then modified with ferric chloride to make it magnetic, and then combined with graphene oxide through electrostatic adsorption and van der Waals interaction. The composite material is then reduced and separated from oxygen atoms by high-temperature calcination to form a nano-scale montmorillonite-iron tetroxide-graphene composite material; this composite material improves the agglomeration of graphene in polyvinyl chloride, and graphene and montmorillonite work synergistically to effectively improve the high temperature resistance of the cable material; the composite material and the free radicals on the surface of titanium dioxide are firmly combined on its concave surface to achieve an anti-cracking effect. DETAILED DESCRIPTION

[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0018] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of a crack-resistant and high-temperature resistant cable material prepared in the following examples are as follows: High temperature resistance: The raw materials prepared in the examples and comparative examples were made into test samples according to GB / T2951.11-2008 and placed on a clean glass plate. When the temperature of the heat aging test box was raised to about 200°C, the glass plate was quickly placed in it. When the temperature reached 200°C, the timing was started. The color change was observed carefully. The time required for the color to start to turn slightly yellow was recorded as the thermal stability time at 200°C.

[0019] Mechanical properties: The raw materials prepared in the embodiments and comparative examples were made into test samples according to GB / T2951.11-2008 and molded into 5B dumbbell-shaped specimens on a molding machine. The cut specimens were conditioned at 25°C and 65% relative humidity for 16 h, and mechanical properties were tested on a universal material testing machine to detect the tensile strength and elongation at break of the samples. The test speed was 10 mm / min, and each group of samples was tested 5 times to take the average value.

[0020] Example 1; (1) At 25°C, γ-methacryloxypropyltrimethoxysilane was mixed with deionized water and ethanol to prepare a 2% modifier alcohol aqueous solution, wherein the mass ratio of deionized water to ethanol in the modifier alcohol aqueous solution was 1:5; after hydrolysis for 15 minutes, glass fiber accounting for 30% of the mass of the modifier alcohol aqueous solution was added, and the solution was immersed at 80°C for 6 hours and then taken out, and then placed in a vacuum drying oven at 120°C for 1 hour, with a vacuum degree of 0.085 MPa, to allow it to fully react and obtain pretreated glass fiber; 1 part of the pretreated glass fiber was added to 50 parts of deionized water, mechanically stirred at 60 rpm and heated to 80°C, with a heating rate of 10°C / min, 0.5 parts of oleic acid was added dropwise, and then the solution was kept warm for reaction for 6 hours. After the reaction was completed, the solid was taken out and washed with deionized water three times to obtain oleic acid-coated glass fiber; (2) The oleic acid-wrapped glass fiber was fixed at a processing distance of 15 mm by adjusting the height of the moving platform, which is the length of the plasma jet flame. The moving speed of the moving platform was adjusted to control the processing time to 10 s. The working gas flow rate was fixed to 1 L / min. The flow meter was adjusted to control the carrier gas flow rate. The flow rate of titanium chloride was 20 mL / min and the flow rate of water molecules was 80 mL / min. The AC power was turned on to excite the atmospheric pressure plasma jet to generate plasma. Titanium chloride vapor was mixed with argon gas and entered the plasma jet discharge zone together with water molecule vapor. It was transferred to the surface of the oleic acid-wrapped glass fiber along with the plasma jet flame to form titanium dioxide deposition. The product after deposition was modified and placed on a special transmission device of the plasma treatment equipment. Under atmospheric pressure and open environment, the plasma was directly sprayed onto the surface of the product. The specific distance below the nozzle of the plasma spray device was within 2 cm. The atmosphere was helium. The power was 10 W and the time was 20 s. Glass fiber-titanium dioxide material was prepared. (3) Disperse 2 parts of natural montmorillonite into 50 parts of deionized water and stir at 400 rpm for 1 hour for activation, then add hexadecyltrimethylammonium bromide active agent into the montmorillonite suspension, the mass ratio of hexadecyltrimethylammonium bromide to montmorillonite is 0.05:1, and heat the mixed solution to 75°C and stir at 400 rpm for 2 hours; then filter the resulting solution, wash it with deionized water 3 times, and dry it at 60°C for 6 hours to obtain activated montmorillonite; weigh 2 parts of the activated montmorillonite into 50 parts of deionized water, and stir it magnetically at 150 rpm for 60 minutes at room temperature to obtain an activated montmorillonite suspension; weigh 0.5 parts of ferric chloride solid and dissolve it in 50 parts of deionized water, and ultrasonicate it to make it quickly Dissolve, power is 20kHz, prepare ferric chloride solution; slowly add ferric chloride solution to activated montmorillonite suspension by peristaltic pump, stir at 100rpm for 24h under 60℃ water bath condition, stop stirring after reaction, and continue aging at room temperature for 12h; after aging, centrifuge at 18000rpm for 20min to get solid, wash repeatedly with deionized water 3 times, and then dry at 70℃ for 5h to obtain magnetic montmorillonite; mix 1 part of graphene oxide with 50 parts of deionized water to form a dispersion, and then ultrasonically treat it for 30min at a power of 20kHz, then add 5 parts of magnetic montmorillonite, first ultrasonically treat it for 30min at a power of 20kHz, and then fully stir the mixture at 600rpm for 2h; filter the suspension after reaction and wash it with deionized water 3 times, freeze-dry at -40℃ for 12h, and then calcine it, calcine it at 750℃ for 1h, and take it out to obtain a composite material; (4) Raw materials by weight ratio: 60 parts of polyvinyl chloride SG-3, 0.4 parts of silane coupling agent KH550, 15 parts of polypropylene resin, 2 parts of barium stearate, 2 parts of dimethylaminoethoxyethanol, 2 parts of composite materials, 1 part of glass fiber-titanium dioxide material, 2 parts of epoxy soybean oil, 1 part of antimony trioxide, 5 parts of carbon nanotubes. The materials are mixed in proportion and placed in a centrifuge. After centrifugal stirring at 500 rpm for 10 minutes to mix evenly, the temperature is 160°C, and the mixture is extruded into a molten state in a twin-screw extruder. After the mixture is completely melted, it is extruded into an injection molding machine at an extrusion temperature of 170°C to obtain a crack-resistant and high-temperature resistant cable material.

[0021] Example 2; (1) At 25°C, γ-methacryloxypropyltrimethoxysilane was mixed with deionized water and ethanol to prepare a 5% modifier alcohol aqueous solution, wherein the mass ratio of deionized water to ethanol in the modifier alcohol aqueous solution was 1:5; after hydrolysis for 30 minutes, glass fiber accounting for 35% of the mass of the modifier alcohol aqueous solution was added, and the solution was immersed at 90°C for 8 hours and then taken out, and then placed in a vacuum drying oven at 120°C for 1.5 hours, and the vacuum degree was 0.085 MPa, so as to fully react and obtain pretreated glass fiber; 1.5 parts of the above pretreated glass fiber were added to 50 parts of deionized water, mechanically stirred at 80 rpm and heated to 80°C, and the heating rate was 10°C / min, and 2.25 parts of oleic acid were added dropwise, and then kept warm for reaction for 8 hours. After the reaction was completed, the solid was taken out and washed with deionized water three times to obtain oleic acid-coated glass fiber; (2) The oleic acid-wrapped glass fiber was fixed at a processing distance of 17 mm by adjusting the height of the moving platform, which is the length of the plasma jet flame. The moving speed of the moving platform was adjusted to control the processing time to 12 s. The working gas flow rate was fixed at 2.5 L / min. The flow meter was adjusted to control the carrier gas flow rate. The flow rate of titanium chloride was 40 mL / min and the flow rate of water molecules was 100 mL / min. The AC power was turned on to excite the atmospheric pressure plasma jet to generate plasma. Titanium chloride vapor was mixed with argon gas and entered the plasma jet discharge zone together with water molecule vapor. It was transferred to the surface of the oleic acid-wrapped glass fiber along with the plasma jet flame to form titanium dioxide deposition. The product after deposition was modified and placed on a special transmission device of the plasma treatment equipment. Under atmospheric pressure and open environment, the plasma was directly sprayed onto the surface of the product. The specific distance below the nozzle of the plasma spray device was within 2 cm. The atmosphere was helium. The power was 40 W and the time was 40 s. Glass fiber-titanium dioxide material was prepared. (3) Disperse 2.5 parts of natural montmorillonite in 50 parts of deionized water and stir at 500 rpm for 2 hours for activation. Then add hexadecyl trimethyl ammonium bromide active agent to the montmorillonite suspension. The mass ratio of hexadecyl trimethyl ammonium bromide to montmorillonite is 0.15:1. Heat the mixed solution to 75°C and stir at 500 rpm for 3 hours. Then filter the resulting solution, wash it with deionized water three times, and dry it at 60°C for 8 hours to obtain activated montmorillonite. Weigh 3.5 parts of activated montmorillonite in 50 parts of deionized water and stir it magnetically at 200 rpm for 90 minutes at room temperature to obtain an activated montmorillonite suspension. Weigh 1 part of ferric chloride solid and dissolve it in 50 parts of deionized water. Ultrasound is used to dissolve it quickly at a power of 20 kHz to prepare a ferric chloride solution. Slowly add the ferric chloride solution to the activated montmorillonite suspension by a peristaltic pump and stir it at 150 rpm for 24 hours in a 60°C water bath. h, after the reaction is completed, stirring is stopped, and aging at room temperature is continued for 12 hours; after aging, the solid is centrifuged at 18000rpm for 20 minutes, and the solid is repeatedly washed with deionized water for 3 times, and then dried at 70°C for 5 hours to obtain magnetic montmorillonite; 1 part of graphene oxide is mixed with 50 parts of deionized water to form a dispersion, and then the dispersion is ultrasonically treated for 30 minutes at a power of 20kHz, and then 6.5 parts of magnetic montmorillonite are added, ultrasonically treated for 30 minutes at a power of 20kHz, and then the mixture is fully stirred at 600rpm for 2 hours; the suspension after the reaction is filtered and washed with deionized water for 3 times, freeze-dried at -40°C for 12 hours, and then calcined, calcined at 800°C for 1.5 hours, and the composite material is obtained after the calcination is completed; (4) Raw materials by weight ratio: 70 parts of polyvinyl chloride SG-3, 0.5 parts of silane coupling agent KH550, 15.5 parts of polypropylene resin, 3 parts of barium stearate, 2.5 parts of dimethylaminoethoxyethanol, 3.5 parts of composite material, 2.5 parts of glass fiber-titanium dioxide material, 3 parts of epoxy soybean oil, 1.5 parts of antimony trioxide, 6.5 parts of carbon nanotubes. The materials are mixed in proportion and placed in a centrifuge. After centrifugation at 600 rpm for 20 minutes to mix evenly, the temperature is 170°C, and the mixture is extruded into a molten state in a twin-screw extruder. After the mixture is completely melted, it is extruded into an injection molding machine at an extrusion temperature of 172°C to obtain a crack-resistant and high-temperature resistant cable material.

[0022] Example 3; (1) At 25°C, γ-methacryloxypropyltrimethoxysilane was mixed with deionized water and ethanol to prepare a modifier alcohol aqueous solution with a mass fraction of 8%, wherein the mass ratio of deionized water to ethanol in the modifier alcohol aqueous solution was 1:5; after hydrolysis for 45 minutes, glass fiber accounting for 40% of the mass of the modifier alcohol aqueous solution was added, and the mixture was immersed at 100°C for 10 hours and then taken out, and then placed in a vacuum drying oven at 120°C for 2 hours with a vacuum degree of 0.085 MPa to allow it to fully react to obtain pretreated glass fiber; 2 parts of the above pretreated glass fiber were added to 50 parts of deionized water, mechanically stirred at a speed of 100 rpm and heated to 80°C, the heating rate was 10°C / min, 4 parts of oleic acid were added dropwise, and then the reaction was kept warm for 10 hours. After the reaction was completed, the solid was taken out and washed with deionized water three times to obtain oleic acid-coated glass fiber; (2) The oleic acid-wrapped glass fiber was fixed at a processing distance of 20 mm by adjusting the height of the moving platform, which is the length of the plasma jet flame. The moving speed of the moving platform was adjusted to control the processing time to 14 s. The working gas flow rate was fixed to 4 L / min. The flow meter was adjusted to control the carrier gas flow rate. The flow rate of titanium chloride was 60 mL / min and the flow rate of water molecules was 120 mL / min. The AC power was turned on to excite the atmospheric pressure plasma jet to generate plasma. Titanium chloride vapor was mixed with argon gas and entered the plasma jet discharge zone together with water molecule vapor. It was transferred to the surface of the oleic acid-wrapped glass fiber along with the plasma jet flame to form titanium dioxide deposition. The product after deposition was modified and placed on a special transmission device of the plasma treatment equipment. Under atmospheric pressure and open environment, the plasma was directly sprayed onto the surface of the product. The specific distance below the nozzle of the plasma spray device was within 2 cm. The atmosphere was oxygen. The power was 70 W and the time was 60 s. Glass fiber-titanium dioxide material was prepared. (3) Disperse 3 parts of natural montmorillonite in 50 parts of deionized water and stir at 600 rpm for 3 hours for activation. Then add hexadecyl trimethyl ammonium bromide active agent to the montmorillonite suspension. The mass ratio of hexadecyl trimethyl ammonium bromide to montmorillonite is 0.25:1. Heat the mixed solution to 75 °C and stir at 600 rpm for 4 hours. Then filter the resulting solution, wash it with deionized water three times, and dry it at 60 °C for 10 hours to obtain activated montmorillonite. Weigh 5 parts of the activated montmorillonite in 50 parts of deionized water and stir it magnetically at 250 rpm for 120 minutes at room temperature to obtain an activated montmorillonite suspension. Weigh 1.5 parts of ferric chloride solid and dissolve it in 50 parts of deionized water. Ultrasound is used to dissolve it quickly at a power of 20 kHz to prepare a ferric chloride solution. Slowly add the ferric chloride solution to the activated montmorillonite suspension by a peristaltic pump and stir it at 200 rpm for 24 hours in a 60 °C water bath. h, after the reaction is completed, stirring is stopped, and aging at room temperature is continued for 12 hours; after aging, the solid is centrifuged at 18000rpm for 20 minutes, and is repeatedly washed with deionized water for 3 times, and then dried at 70°C for 5 hours to obtain magnetic montmorillonite; 1 part of graphene oxide is mixed with 50 parts of deionized water to form a dispersion, and then the dispersion is ultrasonically treated for 30 minutes at a power of 20kHz, and then 8 parts of magnetic montmorillonite are added, ultrasonically treated for 30 minutes at a power of 20kHz, and then the mixture is fully stirred at 600rpm for 2 hours; the suspension after the reaction is filtered and washed with deionized water 3 times, freeze-dried at -40°C for 12 hours, and then calcined, calcined at 850°C for 2 hours, and the composite material is obtained after the calcination is completed; (4) Raw materials by weight ratio: 80 parts of polyvinyl chloride SG-3, 0.6 parts of silane coupling agent KH550, 16 parts of polypropylene resin, 4 parts of barium stearate, 3 parts of dimethylaminoethoxyethanol, 5 parts of composite material, 4 parts of glass fiber-titanium dioxide material, 4 parts of epoxy soybean oil, 2 parts of antimony trioxide, 8 parts of carbon nanotubes. The materials are mixed in proportion and placed in a centrifuge. After centrifugal stirring at 700 rpm for 30 minutes to mix evenly, the temperature is 180°C, and the mixture is extruded into a molten state in a twin-screw extruder. After the mixture is completely melted, it is extruded into an injection molding machine at an extrusion temperature of 175°C to obtain a crack-resistant and high-temperature resistant cable material.

[0023] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that steps (2) (4) are different, and steps (2) (4) are changed to: (2) placing oleic acid-coated glass fiber on a dedicated transmission device of a plasma treatment device, and directly spraying plasma onto the surface of the product under atmospheric pressure and an open environment, within a specific distance of 2 cm below the nozzle of the plasma spraying device, with an atmosphere of helium, a power of 40 W, and a time of 40 s, to prepare a composite glass fiber material; (4) Raw materials by weight ratio: 70 parts of polyvinyl chloride SG-3, 0.5 parts of silane coupling agent KH550, 15.5 parts of polypropylene resin, 3 parts of barium stearate, 2.5 parts of dimethylaminoethoxyethanol, 3.5 parts of composite material, 2.5 parts of composite glass fiber material, 3 parts of epoxy soybean oil, 1.5 parts of antimony trioxide, 6.5 parts of carbon nanotubes. The materials are mixed in proportion and placed in a centrifuge. After centrifugation and stirring at 600 rpm for 20 minutes, the mixture is evenly mixed and then the temperature is 170°C. The mixture is extruded into a molten state in a twin-screw extruder. After the mixture is completely melted, it is extruded into an injection molding machine at an extrusion temperature of 172°C to obtain a crack-resistant and high-temperature resistant cable material. The remaining steps are the same as those in Example 2.

[0024] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that steps (1) and (2) are different, and steps (1) and (2) are changed to: (1) at 25°C, γ-methacryloxypropyltrimethoxysilane is mixed with deionized water and ethanol to prepare a modifier alcohol aqueous solution with a mass fraction of 5%, and the mass ratio of deionized water to ethanol in the modifier alcohol aqueous solution is 1:5; after hydrolysis for 30 minutes, glass fiber accounting for 35% of the mass of the modifier alcohol aqueous solution is added, and the mixture is immersed at 90°C for 8 hours, then taken out, and then placed in a vacuum drying oven at 120°C for 1.5 hours, and the vacuum degree is 0.085MPa, so that it is fully reacted to obtain pretreated glass fiber; (2) The pretreated glass fiber was fixed to a treatment distance of 17 mm by adjusting the height of the moving platform, which is the length of the plasma jet flame. The moving speed of the moving platform was adjusted to control the treatment time to 12 s. The working gas flow rate was fixed to 2.5 L / min. The flow meter was adjusted to control the carrier gas flow rate. The flow rate of titanium chloride was 40 mL / min and the flow rate of water molecules was 100 mL / min. The AC power was turned on to excite the atmospheric pressure plasma jet to generate plasma. Titanium chloride vapor was mixed into argon gas and entered the plasma jet discharge zone together with water molecule vapor. The vapor was transferred to the surface of the oleic acid-coated glass fiber along with the plasma jet flame to form titanium dioxide deposition. The product after the deposition was modified and placed on a special transmission device of the plasma treatment equipment. The plasma was directly sprayed onto the surface of the product under atmospheric pressure and in an open environment. The plasma was sprayed within a specific distance of 2 cm below the nozzle of the plasma spray device. The atmosphere was helium. The power was 40 W and the time was 40 s. The glass fiber-titanium dioxide material was prepared. The remaining steps were the same as those in Example 2.

[0025] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that step (2) is different. Step (2) is changed to: the oleic acid-wrapped glass fiber is fixed to a processing distance of 17 mm by adjusting the height of the moving platform, which is the length of the plasma jet flame, and the moving speed of the moving platform is adjusted to control the processing time to 12 s. The working gas flow rate is fixed to 2.5 L / min, and the flow meter is adjusted to control the carrier gas flow rate. The flow rate of titanium chloride is 40 mL / min, and the flow rate of water molecules is 100 mL / min; the AC power supply is turned on to excite the atmospheric pressure plasma jet to generate plasma, and the titanium chloride vapor is mixed into the argon gas and enters the plasma jet discharge zone together with the water molecule vapor. Along with the plasma jet flame, it is transferred to the surface of the oleic acid-wrapped glass fiber to form titanium dioxide deposition, and a glass fiber-titanium dioxide material is prepared; the remaining steps are the same as those in Example 2.

[0026] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that step (1) is different. Step (1) is changed to: at 25°C, 1.5 parts of glass fiber are added to 50 parts of deionized water, and the mixture is mechanically stirred at 80 rpm and heated to 80°C. The heating rate is 10°C / min, and 2.25 parts of oleic acid are added dropwise. The mixture is then kept warm for 8 hours. After the reaction is completed, the solid is taken out and washed with deionized water three times to obtain oleic acid-coated glass fiber. The remaining steps are the same as those in Example 2.

[0027] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that step (3) is different. Step (3) is changed to: 2.5 parts of natural montmorillonite are dispersed in 50 parts of deionized water and stirred at 500 rpm for 2 hours for activation, and then cetyl trimethyl ammonium bromide active agent is added to the montmorillonite suspension, the mass ratio of cetyl trimethyl ammonium bromide to montmorillonite is 0.15:1, and the mixed solution is heated to 75°C and stirred at 500 rpm for 3 hours; then the obtained solution is filtered, washed with deionized water 3 times, and dried at 60°C, 8 h, to obtain activated montmorillonite; 1 part of graphene oxide was mixed with 50 parts of deionized water to form a dispersion, and then ultrasonically treated for 30 min at a power of 20 kHz, and then 6.5 parts of activated montmorillonite were added, and ultrasonically treated for 30 min at a power of 20 kHz, and then the mixture was fully stirred at a speed of 600 rpm for 2 h; the suspension after the reaction was filtered and washed with deionized water 3 times, freeze-dried at -40°C for 12 h, and then calcined, calcined at 800°C for 1.5 h, and then taken out to obtain a composite material; the remaining steps are the same as those in Example 2.

[0028] Effect example Table 1 below shows the performance analysis results of a crack-resistant and high-temperature resistant cable material using Examples 1 to 3 of the present invention and Comparative Examples 1 to 5.

[0029] Table 1

[0030] From the comparison of the experimental data of the mechanical properties of the embodiment and the comparative example, it can be found that the present invention firstly performs surface modification on the glass fiber with γ-methacryloxypropyltrimethoxysilane to increase the active groups on the surface of the glass fiber, and then wraps the glass fiber by reacting oleic acid with the active groups on the surface. The glass fiber wrapped with oleic acid improves its bonding strength in polyvinyl chloride and more effectively exerts its mechanical properties of improving the crack resistance of the cable material; after titanium dioxide is deposited on the surface of the glass fiber, a secondary plasma treatment is performed, and the sprayed plasma not only forms free radicals on the surface of titanium dioxide, but also forms depressions on the surface of titanium dioxide due to the impact of ion beams, providing chemical binding sites, which is beneficial to the subsequent bonding of the composite material; the composite material and the free radicals on the surface of titanium dioxide are firmly bonded to the surface of the depression, achieving the anti-cracking effect. From the comparison of the experimental data of the high temperature resistance of the embodiment and the comparative example, it can be found that the present invention uses an atmospheric pressure plasma jet to deposit titanium dioxide on the surface of the glass fiber wrapped by oleic acid, and a water-oil interface is formed due to the presence of surface oleic acid. The titanium dioxide synthesized by dehydration and condensation of the titanium precursor and the mist-like water molecules forms a polyhedral structure of stacked sheets, which has a nanometer-level reaction space. This three-dimensional structure of titanium dioxide improves the thermal stability and mechanical properties of the cable material; then the natural nano-montmorillonite is dispersed in water for activation, and then modified by ferric chloride to make it magnetic, and then combined with graphene oxide through electrostatic adsorption and van der Waals force interaction, and then the composite material is reduced and separated from oxygen atoms by high-temperature calcination to form a nano-level montmorillonite-iron tetroxide-graphene composite material; this composite material improves the agglomeration of graphene in polyvinyl chloride, and the graphene and montmorillonite act synergistically at the same time to effectively improve the high temperature resistance of the cable material.

[0031] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing a crack-resistant and high-temperature resistant cable material, characterized in that: The method comprises the following preparation steps: (1) At 25°C, γ-methacryloxypropyltrimethoxysilane is mixed with deionized water and ethanol to prepare a modifier alcohol aqueous solution with a mass fraction of 2-8%, and after hydrolysis for 15-45 minutes, glass fibers accounting for 30-40% of the mass of the modifier alcohol aqueous solution are added, and the solution is immersed at 80-100°C for 6-10 hours, then taken out, and then placed in a vacuum drying oven at 120°C for 1-2 hours to fully react to obtain pretreated glass fibers; 1-2 parts of the pretreated glass fibers are added to 50 parts of deionized water, mechanically stirred at a speed of 60-100 rpm and heated to 80°C, and then 0.5-4 parts of oleic acid are added dropwise, and then the solution is kept warm for reaction for 6-10 hours. After the reaction is completed, the solid is taken out and washed with deionized water for 3 times to obtain oleic acid-coated glass fibers; (2) The oleic acid-wrapped glass fiber is fixed at a processing distance of 15-20 mm by adjusting the height of the moving platform, which is the length of the plasma jet flame. The moving speed of the moving platform is adjusted to control the processing time to 10-14 s. The working gas flow rate is fixed to 1-4 L / min. The flow meter is adjusted to control the carrier gas flow rate. The flow rate of titanium chloride is 20-60 mL / min, and the flow rate of water molecules is 80-120 mL / min. Turn on the AC power supply to excite the atmospheric pressure plasma jet to generate plasma. Titanium chloride vapor is mixed with the inert gas and enters the plasma jet discharge zone together with the water molecule vapor. It is transferred to the surface of the oleic acid-wrapped glass fiber along with the plasma jet flame to form titanium dioxide deposition. Then, the product after the deposition is modified and placed on a special transmission device of the plasma treatment equipment. Under atmospheric pressure and open environment, the plasma is directly sprayed onto the surface of the product at a power of 10-70 W for 20-60 s to prepare a glass fiber-titanium dioxide material. (3) Disperse 2-3 parts of natural montmorillonite into 50 parts of deionized water and stir at 400-600 rpm for 1-3 hours for activation, then add a certain amount of hexadecyltrimethylammonium bromide active agent to the montmorillonite suspension, and heat the mixed solution to 75°C and stir at 400-600 rpm for 2-4 hours; then filter the resulting solution, wash it with deionized water three times, and dry it at 60°C for 6-10 hours to obtain activated montmorillonite; weigh 2-5 parts of the activated montmorillonite into 50 parts of deionized water, and stir it magnetically at 150-250 rpm for 60-120 minutes at room temperature to obtain an activated montmorillonite suspension; weigh 0.5-1.5 parts of ferric chloride solid and dissolve it in 50 parts of deionized water, and dissolve it quickly by ultrasound to prepare a ferric chloride solution; slowly add the ferric chloride solution into the activated montmorillonite suspension by a peristaltic pump, and stir it at 100-200 rpm for 24 hours in a water bath at 60°C. h, after the reaction is completed, stirring is stopped, and aging at room temperature is continued for 12 hours; after aging, the solid is centrifuged at 18000rpm for 20 minutes, and the solid is repeatedly washed with deionized water for 3 times, and then dried at 70°C for 5 hours to obtain magnetic montmorillonite; 1 part of graphene oxide is mixed with 50 parts of deionized water to form a dispersion, and then ultrasonically treated for 30 minutes, and then 5-8 parts of magnetic montmorillonite are added, ultrasonically treated for 30 minutes, and then the mixture is fully stirred at 600rpm for 2 hours; the suspension after the reaction is filtered and washed with deionized water for 3 times, freeze-dried, and then calcined at 750-850°C for 1-2 hours, and the composite material is obtained after the calcination is completed; (4) Raw materials by weight ratio: 60-80 parts of polyvinyl chloride SG-3, 0.4-0.6 parts of silane coupling agent KH550, 15-16 parts of polypropylene resin, 2-4 parts of barium stearate, 2-3 parts of dimethylaminoethoxyethanol, 2-5 parts of composite material, 1-4 parts of glass fiber-titanium dioxide material, 2-4 parts of epoxy soybean oil, 1-2 parts of antimony trioxide, 5-8 parts of carbon nanotubes. The materials are mixed in proportion and placed in a centrifuge. After centrifugation and stirring at 500-700 rpm for 10-30 minutes to mix evenly, the temperature is 160-180°C, and the mixture is extruded into a molten state in a twin-screw extruder. After the mixture is completely melted, it is extruded into an injection molding machine to obtain a crack-resistant and high-temperature resistant cable material.

2. The method for preparing a crack-resistant and high-temperature resistant cable material according to claim 1, characterized in that: In the step (1), the mass ratio of deionized water to ethanol in the aqueous alcohol solution of the modifier is 1:

5.

3. The method for preparing a crack-resistant and high-temperature resistant cable material according to claim 1, characterized in that: The vacuum degree of the vacuum drying oven in step (1) is 0.085 MPa.

4. The method for preparing a crack-resistant and high-temperature resistant cable material according to claim 1, characterized in that: The heating rate in step (1) is 10°C / min.

5. The method for preparing a crack-resistant and high-temperature resistant cable material according to claim 1, characterized in that: The inert gas in step (2) is argon.

6. The method for preparing a crack-resistant and high-temperature resistant cable material according to claim 1, characterized in that: During the modification in step (2), the atmosphere is helium or oxygen within a specific distance of 2 cm below the nozzle of the plasma jet device.

7. The method for preparing a crack-resistant and high-temperature resistant cable material according to claim 1, characterized in that: In the step (3), the mass ratio of hexadecyltrimethylammonium bromide to montmorillonite is 0.05-0.25:

1.

8. The method for preparing a crack-resistant and high-temperature resistant cable material according to claim 1, characterized in that: The ultrasonic power in step (3) is 20 kHz.

9. The method for preparing a crack-resistant and high-temperature resistant cable material according to claim 1, characterized in that: The freeze drying in step (3) is freeze drying at -40°C for 12 hours.

10. The method for preparing a crack-resistant and high-temperature resistant cable material according to claim 1, characterized in that: The extrusion temperature in step (4) is 170-175°C.

Citation Information

Patent Citations

  • Insulation cable material and preparation method thereof

    CN104119624A

  • Composite modified montmorillonite magnetic adsorbent as well as preparation method and application thereof

    CN111871377A

  • Preparation method of intercalation modified montmorillonite / cassava starch composite film

    CN113150393A

  • Bending-resistant winding core pipe and preparation method thereof

    CN118909350A

  • Preparation method of muscone

    CN118993864A

Cited By

  • A modified polyethylene trenchless pipe composite material and its preparation method

    CN122668464A